The Existence of Mandiri Lestari Waste Bank Management in Supporting Sustainable Development of Mapanget District, Manado City - Rombang, Robert F. M.; Mandagi, Martinus; Tumbel, Goinpeace H. (Technium Social Sciences Journal, 2024)
Waste that is not managed properly will have an impact on the environment and also on public health. Waste Management is a systematic, comprehensive, and sustainable activity that includes reducing and handling waste. The aims of this research are: 1) to find out, describe, and analyze Waste Management at the Mandiri Lestari Waste Bank; 2) to find out and describe waste bank management in supporting sustainable development in Mapanget District, Manado City. This research uses qualitative methods with data collection techniques in the form of observation, interviews, and documentation. The research results show that 1) Mandiri Lestari Waste Bank management is not optimal, this can be seen from inadequate management, facilities, and governance that are not in accordance with existing regulations; 2) The management of the Mandiri Lestari Waste Bank is not yet supported by all groups, including the community, government and waste bank managers. Good waste bank management will improve the economy and development for the communities involved and can improve the quality of life with a clean environment.